Validation of a new technique to detect Cryptosporidium spp. oocysts in bovine feces - Inácio, Sandra Valéria [UNESP]; Gomes, Jancarlo Ferreira; Oliveira, Bruno César Miranda [UNESP]; Falcão, Alexandre Xavier; Suzuki, Celso Tetsuo Nagase; dos Santos, Bianca Martins; de Aquino, Monally Conceição Costa [UNESP]; de Paula Ribeiro, Rafaela Silva [UNESP]; de Assunção, Danilla Mendes [UNESP]; Casemiro, Pamella Almeida Freire [UNESP]; Meireles, Marcelo Vasconcelos [UNESP]; Bresciani, Katia Denise Saraiva [UNESP] (Elsevier, 2016)
Due to its important zoonotic potential, cryptosporidiosis arouses strong interest in the scientific community, because, it was initially considered a rare and opportunistic disease. The parasitological diagnosis of the causative agent of this disease, the protozoan Cryptosporidium spp., requires the use of specific techniques of concentration and permanent staining, which are laborious and costly, and are difficult to use in routine laboratory tests. In view of the above, we conducted the feasibility, development, evaluation and intralaboratory validation of a new parasitological technique for analysis in optical microscopy of Cryptosporidium spp. oocysts, called TF-Test Coccidia, using fecal samples from calves from the city of Araçatuba, São Paulo. To confirm the aforementioned parasite and prove the diagnostic efficiency of the new technique, we used two established methodologies in the scientific literature: parasite concentration by centrifugal sedimentation and negative staining with malachite green (CSN-Malachite) and Nested-PCR. We observed good effectiveness of the TF-Test Coccidia technique, being statistically equivalent to CSN-Malachite. Thus, we verified the effectiveness of the TF-Test Coccidia parasitological technique for the detection of Cryptosporidium spp. oocysts and observed good concentration and morphology of the parasite, with a low amount of debris in the fecal smear.
Keywords: Coccidiosis; Diagnostic; Parasites